2021
DOI: 10.1016/j.chest.2021.01.084
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Pruning and Longitudinal Change in Percent Emphysema and Lung Function

Abstract: BACKGROUND: Pulmonary endothelial damage has been shown to precede the development of emphysema in animals, and vascular changes in humans have been observed in COPD and emphysema.RESEARCH QUESTION: Is intraparenchymal vascular pruning associated with longitudinal progression of emphysema on CT imaging or decline in lung function over 5 years?STUDY DESIGN AND METHODS: The Genetic Epidemiology of COPD Study enrolled ever smokers with and without COPD from 2008 through 2011. The percentage of emphysemalike lung,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Most of the studies found that %CSA<5mm 2 or BV5 was positively correlated with FEV1 and FEV1/FVC, but negatively correlated with LAA%-950. 25–30 However, relevant studies on IPVV in smokers or patients with COPD found that the total IPVV was positively correlated with smoking severity and LAA%-950, which was consistent with the results of the correlation analysis on IPVV and emphysema in this study. 31–33 It suggested that small peripheral pulmonary vessels were susceptible to emphysema and hypoxia leading to loss, narrowing, or decreased filling.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the studies found that %CSA<5mm 2 or BV5 was positively correlated with FEV1 and FEV1/FVC, but negatively correlated with LAA%-950. 25–30 However, relevant studies on IPVV in smokers or patients with COPD found that the total IPVV was positively correlated with smoking severity and LAA%-950, which was consistent with the results of the correlation analysis on IPVV and emphysema in this study. 31–33 It suggested that small peripheral pulmonary vessels were susceptible to emphysema and hypoxia leading to loss, narrowing, or decreased filling.…”
Section: Discussionsupporting
confidence: 92%
“…Arteries and veins may be automatically mapped, peripherally matched, and classified ( 174 ). Loss of pulmonary vascular density or distal PA blood volume is associated with right heart failure indices in smokers ( 175 ), emphysema progression ( 176 ), and asthma severity ( 177 ).…”
Section: Assessing the Vasculaturementioning
confidence: 99%
“…Other considerations suggested by the authors included occult cardiovascular disease and abnormal gas mixing with relatively preserved lung mechanics. The authors propose that the consistent association in the entire cohort between low KCO (and DLCO) and high nadir VE/VCO2 implicates pulmonary microvascular dysfunction 22,[24][25][26][47][48][49] as the primary pathogenic mechanism. The authors point out that past studies have shown that in GOLD stage 1 COPD, high nadir VE/VCO2 is primarily influenced by elevated physiologic dead space reflecting abnormally high ventilation/perfusion (V/Q) (presumably secondary to reduced perfusion secondary to microvascular dysfunction) and to a lesser extent a low regulated level of arterial CO2.…”
Section: Measurements and Main Resultsmentioning
confidence: 98%
“…microvascular dysfunction. 12,14,17,[22][23][24][25][26] Other studies have examined the ventilatory efficiency--(minute ventilation [VE] to carbon dioxide production [VCO2]) VE/VCO2 nadir: the lowest ventilatory rate able to remove 1 liter of CO2 per minute during graded cardiopulmonary exercise testing (CPET). [27][28][29][30][31] While many clinicians are familiar with the concept of dynamic hyperinflation that can lead to breath stacking and dyspnea, fewer non-pulmonary physicians are familiar with the assessment of ventilatory efficiency.…”
Section: Introductionmentioning
confidence: 99%